Effect of Rearing, Physiological, and Processing Conditions on the Volatile Profile of Atlantic Salmon (Salmo salar) Using SIFT-MS - Manpreet Kaur; Konrad Dabrowski; Kevin J. Fisher; Md Zakir Hossain; Sheryl Barringer (Foods)
This study examined the effects of rearing, physiological, and processing conditions on the volatile profile of Atlantic salmon. Fish were reared under two different temperature and light conditions, and three harvests were conducted at different time points for male and female fish. Fish were processed to yield fillets with or without skin. Volatiles were analyzed using SIFT-MS headspace analysis. Atlantic salmon reared in cooler temperatures under a 12 h light/dark cycle exhibited significantly lower concentrations of off-odor volatiles compared to those reared in warm conditions under continuous light, suggesting that cooler temperatures with a dark cycle help maintain freshness. A temperature shift from cool to warm further increased volatile accumulation. Longer rearing time resulted in higher volatile concentrations, attributed to greater biochemical products, increased susceptibility to lipid oxidation, protein degradation, and contaminant accumulation from the rearing environment. Males had higher volatile levels at 202 days, while females surpassed males by 242 days, likely due to increased biochemical accumulation associated with reproductive development. Fillets with skin exhibited significantly higher concentration of off-odor volatiles. These findings highlight the role of all studied factors in establishing optimum conditions to minimize spoilage-related volatiles and preserve the freshness of Atlantic salmon, with rearing temperature being the most critical factor.